Análisis del área de contenidos digitales desde el Marco de Referencia de la Competencia Digital de los Docentes de la Unidad Educativa Lauro Damerval Ayora en el año lectivo 2022-2023. - Ordoñez Silva, Edgar Ernesto (2023)
Digital Content is a set of knowledge, skills, attitudes and strategies that are required for the use of digital media and Information and Communication Technologies (ICT). Which are necessary to strengthen the teaching-learning process. That is why the following curricular integration work has as its main objective, Analyze the area of digital content from the Framework of Reference of the Digital Competence of Teachers of the Lauro Damerval Ayora Educational Unit in the 2022-2023 school year. The research method is inductive - deductive, with a quantitative approach with an exploratory-descriptive scope, for data collection it was carried out through an online survey built based on the statements of the Framework of Reference for Digital Teaching Competence. , with a population of 47 teachers from the educational institution, for the data collection it was carried out through an online survey, using a Google form, the questions were adapted from the Reference Framework of the Digital Teacher Competence specifically in the area 2 digital content. Finally, it can be mentioned that the teachers of the institution in question are in the experience stage, which indicates that the teachers have acquired experience through the application of knowledge, procedures and attitudes in the use of digital technologies in the teaching practice, mentioning that the educational institution must implement training courses for teachers and thus strengthen knowledge about the safest and most reliable digital content for their best professional performance. Keywords: Digital skills, digital content, ICT.